Eu3+ doped lanthanum oxide nanowhiskers: microwave hydrothermal synthesis, characterization and photoluminescence properties - Murugan, A. Vadivel; Viswanath, Annamraju Kasi; Kakade, Bhalchandra A.; Ravi, V.; Saaminathan, V. (Journal of Physics D-Applied Physics, 2006)
We report here a straightforward and rapid microwave - hydrothermal route providing an easy synthesis of Eu3+ doped La2O3 nanowhiskers. The nanostructured Eu3+ doped La2O3 is characterized by x-ray diffraction studies, scanning electron microscopy and photoluminescence (PL). The emission spectrum shows transitions from the excited 5D(0) state to F-7(J) (J = 0, 1, 2, 3, 4) levels of the Eu3+ ion. The most intense peak around 611 nm is due to the D-5(0) -> F-7(2) transition, expected from the Judd-Ofelt selection rules. PL spectra measurements demonstrate that the lanthanum oxide nanowhisker shows higher PL intensity.

Highly efficient organic-inorganic poly(3,4-ethylenedioxythiophene)-molybdenum trioxide nanocomposite electrodes for electrochemical supercapacitor - Murugan, A. Vadivel; Viswanath, Annamraju Kasi; Gopinath, Chinnakonda S.; Vijayamohanan, K. (Journal of Applied Physics, 2006)
In this paper, we report a highly efficient organic-inorganic nanocomposite electrode with enhanced double layer capacitance, which has been synthesized using 3,4-ethylenedioxythiophene and crystalline molybdenum trioxide (MoO3) in the presence of an external oxidizing agent. The interlayer spacing of MoO3 upon intercalation expands from 6.93 to 13.46 A and is followed by an exfoliation and restacking process. The resulting nanocomposite is characterized by powder x-ray diffraction, scanning electron microscopy, transmission electron microscopy, x-ray photoelectron spectroscopy, and four probe conductivity measurements. The application potential of this nanocomposite as an electrode material for electrochemical supercapacitors has been investigated, highlighting the unusual enhancement of double layer capacitance of poly(3,4-ethylenedioxythiphene) (PEDOT-MoO3) nanocomposites (similar to 300 F g(-1)) compared to that of pristine MoO3 (similar to 40 mF g(-1)). The improved electrochemical performance is attributed to the intercalation of electronically conducting PEDOT between MoO3 layers with enhanced bidimensionality and an increase in the surface area. (c) 2006 American Institute of Physics.

Photoluminescence studies of Eu3+ doped Y2O3 nanophosphor prepared by microwave hydrothermal method - Murugan, A. Vadivel; Viswanath, Annamraju Kasi; Ravi, V.; Kakade, Bhalchandra A.; Saaminathan, V. (Applied Physics Letters, 2006)
In this letter, the authors report the photoluminescence studies of Eu3+ doped Y2O3 nanorods, which have been synthesized by rapid microwave hydrothermal route within 6 min. The nanostructured Eu3+ doped Y2O3 is characterized by x-ray diffraction, transmission electron microscopy, and photoluminescence. The emission spectrum shows transitions from the excited 5D(0) state to F-7(J) (J=0,1,2,3,4) levels of the Eu3+ ion. The most intense peak around 612 nm is due to the D-5(0)-> F-7(2) transition, expected from the Judd-Ofelt selection rules [B. R. Judd, Phys. Rev. 127, 750 (1962); G. S. Ofelt, J. Chem. Phys. 37, 511 (1962)]. Photoluminescence measurements demonstrated that the nanocrystalline Eu3+:Y2O3 phase shows higher photoluminescence intensity. (c) 2006 American Institute of Physics.

Template free synthesis of mesoporous TiO2 with high wall thickness and nanocrystalline framework - Kulkarni, Dhanashree G.; Murugan, A. Vadivel; Viswanath, Annamraju Kasi; Gopinath, Chinnakonda S. (Journal of Nanoscience and Nanotechnology, 2009)
A simple procedure to prepare nanocrystalline mesoporous titania (meso-TiO2) is reported without any templating agent and it possesses a high BET surface area and a large pore wall thickness (11.3 nm) than that of meso-TiO2 prepared by other methods. Nanocrystalline meso-TiO2 also has been synthesized with hexadecylamine template for comparison through known procedure. The meso-TiO2 materials were characterized by X-ray diffraction, FT-IR, UV-Vis absorbance spectra, thermal analysis, SEM, HRTEM and textural properties through N-2 adsorption-desorption isotherms. Spherical shape particles in a range of few hundred nanometers are obtained in the template free method. Above systematic characterization provides direct indications toward the mechanism of formation of meso-TiO2 in the template free method. A comparison of the physical and textural properties indicates a possibility of coarse-tuning of the textural characteristics of mesoporous TiO2 by adopting different preparation methods.
Keywords: Mesopore; Mesopore Formation; Template-Free; Thick Wall; titania

Structure, electronic structure, optical, and dehydrogenation catalytic study of (Zn1-zInz)(O1-xNx) solid solution - Mapa, Maitri; Sivaranjani, Kumarsrinivasan; Bhange, Deu S.; Saha, Biswajit; Chakraborty, Purushottam; Viswanath, Annamraju Kasi; Gopinath, Chinnakonda S. (Chemistry of Materials, 2010)
Indium and nitrogen codoping in ZnO leads to a solid solution of InN in ZnO with I composition of(Zn1-zInz)(O1-xNx). A simple solution combustion method has been adopted to prepare the above materials in less than 10 min with metal nitrates as the metal loll source and urea as fuel. With reference to ZnO, significant increase in lattice parameters was observed with increasing In-content. However, the In2O3 phase was Observed along with InN for]it content >= 10%. Optical absorption extended into the Visible region, at least LIP to 550 nm, demonstrates an effective reduction of optical band gap due to the formation of solid Solution. A new feature observed just above O2p valence band in X-ray photoelectron spectroscopy (XPS) suggests the creation of N 2p states from InN; the N Is core level XPS result too confirms nitride contribution. Raman spectroscopy and secondary ion mass spectrometry results show direct In-N, Zn-N. and In-N-Zn fragments in (Zn1-zInz)(O1-x,N-x). Catalytic activity explored for Oxidation of 2-butanol to ethyl methyl ketone demonstrates a high selectivity at 350 and 400 degrees C. All of the above characteristics suggest the multifunctional nature of (Zn1-zInz)(O1-xNx) and its potential for other applications.